Challenges and recommendations for the development of cultural control of aerial oomycete-associated diseases in protected horticulture - Andrew M. Beacham; Katy L. James; Nicola P. Randall; James M. Monaghan (European Journal of Plant Pathology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Hydroclimatic changes in Alaska portrayed by a high-resolution regional climate simulation - Andrew J. Newman; Andrew J. Monaghan; Martyn P. Clark; Kyoko Ikeda; Lulin Xue; Ethan D. Gutmann; Jeffrey R. Arnold (Climatic Change, 2021)

How will rainfall change over Hawai‘i in the future? High-resolution regional climate simulation of the Hawaiian Islands - Lulin Xue; Yaping Wang; Andrew J. Newman; Kyoko Ikeda; Roy M. Rasmussen; Thomas W. Giambelluca; Ryan J. Longman; Andrew J. Monaghan; Martyn P. Clark; Jeffrey R. Arnold (Bulletin of Atmospheric Science and Technology, 2020)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Interactions between parental traits, environmental harshness and growth rate in determining telomere length in wild juvenile salmon - D. McLennan; J. D. Armstrong; D. C. Stewart; S. Mckelvey; W. Boner; P. Monaghan; N. B. Metcalfe (Molecular Ecology, 2016)
A larger body size confers many benefits, such as increased reproductive success, ability to evade predators and increased competitive ability and social status. However, individuals rarely maximize their growth rates, suggesting that this carries costs. One such cost could be faster attrition of the telomeres that cap the ends of eukaryotic chromosomes and play an important role in chromosome protection. A relatively short telomere length is indicative of poor biological state, including poorer tissue and organ performance, reduced potential longevity and increased disease susceptibility. Telomere loss during growth may also be accelerated by environmental factors, but these have rarely been subjected to experimental manipulation in the natural environment. Using a wild system involving experimental manipulations of juvenile Atlantic salmon Salmo salar in Scottish streams, we found that telomere length in juvenile fish was influenced by parental traits and by direct environmental effects. We found that faster‐growing fish had shorter telomeres and there was a greater cost (in terms of reduced telomere length) if the growth occurred in a harsher environment. We also found a positive association between offspring telomere length and the growth history of their fathers (but not mothers), represented by the number of years fathers had spent at sea. This suggests that there may be long‐term consequences of growth conditions and parental life history for individual longevity.

Projected impact of twenty-first century ENSO changes on rainfall over Central America and northwest South America from CMIP5 AOGCMs - Daniel F. Steinhoff; Andrew J. Monaghan; Martyn P. Clark (Climate Dynamics, 2015)

Inter- and intra-year variation in foraging areas of breeding kittiwakes (Rissa tridactyla) - G. S. Robertson; M. Bolton; W. J. Grecian; P. Monaghan (Marine Biology, 2014)

Effects of exogenous abscisic acid and gibberellic acid on pre-maturity α-amylase formation in wheat grains - K. R. Kondhare; P. S. Kettlewell; A. D. Farrell; P. Hedden; J. M. Monaghan (Euphytica, 2012)

Control of triceps surae stimulation based on shank orientation using a uniaxial gyroscope during gait - C. C. Monaghan; W. J. B. M. van Riel; P. H. Veltink (Medical & Biological Engineering & Computing, 2009)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Modeling the Effects of Limiting the Number of Visitors on Failure Rates of Seabird Nests - COLIN M. BEALE; P. MONAGHAN (Conservation Biology, 2005)
Most attempts to manage disturbance by visitors to nature reserves concentrate on limiting visitor access in some way, which is often unpopular with both visitors and managers. In a few nature reserves the daily numbers of visitors are limited, an action that need not necessarily reduce the total number of visitors. As a test of the assumptions that underlie this management practice, we examined the relationship between daily visitor numbers and daily failure rates of nests in two species of seabirds. Daily failure rates for Black‐legged Kittiwakes (Rissa tridactyla) were weakly correlated with daily visitor numbers but indicated that capping daily visitor numbers slightly reduced overall breeding success. This was not the case for Common Murres (Uria aalge), where failure rate declined seasonally but was not significantly correlated with visitor numbers. For some species, it appears that capping daily visitor numbers may have small conservation costs.

Intra-specific interactions influence egg composition in the lesser black-backed gull (Larus fuscus) - Nanette Verboven; Neil P. Evans; Liliana D’Alba; Ruedi G. Nager; Jonathan D. Blount; Peter F. Surai; Pat Monaghan (Behavioral Ecology and Sociobiology, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Parental condition, brood sex ratio and differential young survival: an experimental study in gulls ( Larus fuscus ) - R. G. Nager; P. Monaghan; D. C. Houston; M. Genovart (Behavioral Ecology and Sociobiology, 2000)

Seabirds and sandeels: the conflict between exploitation and conservation in the northern North Sea - P. Monaghan (Biodiversity and Conservation, 1992)